Validación del método analítico por espectrofotometría infrarroja para la cuantificación de simeticona en suspensión” - Arias Aguilar, Rosa Elena (2009)
In this study, the analytical method was validated by infrared spectrophotometry for quantification of simeticone in suspension, in order to demonstrate its analytical applications. For the analysis, we used a mixture of hexane and hydrochloric acid q.p.reagents. The method was validated by analyzing parameters such as: selectivity, linearity, precision (repeatability and reproducibility) and accuracy. It was demonstrated the analytical method is selective, since there was no evidence of matrix’s interference or degraded products in the quantification of the active ingredient. It yields a linear correlation coefficient r = 0,9999 and a determination coefficient r2 = 0,9989; the statistical test of linearity and the response factor, expressed agreement. The method is precised, the results were repeated with a relative standard deviation of 0,5075%. Finally; the accuracy essay indicated the recovery percentage was 100,11%. The Cochran G test showed the table’s t was smaller than the experimental table’s G (0,73 < 0,9669), and the Student statistic t test showed the table’s t was smaller than experimental table’s t (0,1255 < 2,571). The accuracy was correct according to specifications. The Validate certain parameters allow us to determinate validated the analytical method for quantification of simeticone in suspension.